Research of mathematical models of transmission lines for electromagnetic transient simulations in power systems - Leon Colqui, Jaimis Sajid (2019)
In this work three mathematical models of transmission lines are shown, the most used, to simulate electromagnetic transients in power systems. In addition, its main characteristics, advantages and disadvantages are mentioned. Likewise, the algorithms are shown in the form of flow charts for the simulations of the transients. Finally, the results of simulations of maneuvering surges in a single-phase transmission line using the MATLAB software are shown.